(3GdeSJQTO hHZjI GdQGTOs - (3GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdYdhj, CHh eMeO, GdeYQha HGdQSj,J (B246 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf cJGH GdQO Ydi ef QZe Cf Gddg ai GdSeGA Ohf eG ShGgG ef bhd GdEeGe GdCYXe s
(3BNQgG (B:s
(3hgPG cdg YGQV hdcf LQJ eSFdJfG Edjg hGdMeO ddg QH GdYGdejf hdG Mhd hdGbhI EdG HGddg GdYdi GdYXje s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B91s
Keywords: (3Gdabg GdESdGejs